A narrative review of the literature on the pediatric orthopedic management of fibrous dysplasia - Paris, Elio; De Marco, Giacomo; Vazquez, Oscar; Steiger, Christina; Boudabbous, Sana; Dayer, Romain; Ceroni, Dimitri (Frontiers in Pediatrics, 2025)
Fibrous dysplasia is a congenital, non-inherited, benign intramedullary bone lesion in which the normal bone marrow is replaced by abnormal fibro-osseous tissue. The disorder can be monostotic (involving a single bone) or polyostotic (involving multiple bones). As the abnormal fibro-osseous tissue compromises the mechanical strength of bone, it can result in pain, deformity, fractures, or abnormalities in bone mechanics with inappropriate bone alignment. This narrative review attempts to summarize more than 20 years of observations of patients with FD to help pediatric orthopedists establish a care framework that can improve its identification, understand the impact that endocrinopathies can have on its clinical presentation, and optimize the management of bone disorders. Our focus is specifically on orthopedic manifestations of FD and modern management alternatives. The past 20 years have provided major advances in understanding of fibrous dysplasia (FD), and it is clear that the pediatric orthopedist's role remains highly relevant in the management of all types of FD. Surgical treatment remains appropriate when pain is unresponsive to other medical treatments, when a pathological fracture is impending or has happened, when a deformity is worsening or has formed, or when there is a suspicion of malignant transformation. The pediatric orthopedist must be aware, therefore, of the particularities of the different bones on which they may be called to intervene, and they should give very careful consideration to their operative strategy, which must be adjusted to the biological and static characteristics of the bone.